2016
DOI: 10.1186/s12909-016-0539-y
|View full text |Cite
|
Sign up to set email alerts
|

Cynicism and other attitudes towards patients in an emergency department in a middle eastern tertiary care center

Abstract: BackgroundA caring, compassionate practitioner of the medical arts is the idealized version of what makes a good doctor. If asked to think of a painting of a doctor we most likely conjure an image of a physician sitting at a patient’s bedside checking the pulse with a concerned look on his face. The reality is however that cynicism, among other negative attitudes, is becoming more prominent among physicians and medical staff. The causes and extent of cynicism likely vary among medical departments and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 35 publications
1
22
0
5
Order By: Relevance
“…Finally, a small number of predominantly qualitative studies showed spirituality 89 , 136 , meaning 136 , and religiosity 137 to predict greater ECRC, although there was no effect of religion 39 . The evidence regarding factors such as living situation 39 , 42 , 72 , 82 , upbringing 98 , 113 , 131 , siblings 64 , 76 , having children 39 , 41 , 49 , 64 , 77 , 111 – 113 , 138 , 139 , the number of children 72 , 82 , 84 , 140 , and marital status 43 , 47 , 49 , 50 , 63 , 64 , 72 , 76 , 77 , 83 , 84 , 86 was conflicted and, hence, inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a small number of predominantly qualitative studies showed spirituality 89 , 136 , meaning 136 , and religiosity 137 to predict greater ECRC, although there was no effect of religion 39 . The evidence regarding factors such as living situation 39 , 42 , 72 , 82 , upbringing 98 , 113 , 131 , siblings 64 , 76 , having children 39 , 41 , 49 , 64 , 77 , 111 – 113 , 138 , 139 , the number of children 72 , 82 , 84 , 140 , and marital status 43 , 47 , 49 , 50 , 63 , 64 , 72 , 76 , 77 , 83 , 84 , 86 was conflicted and, hence, inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…This occurs because medical students will try to survive the demands in a medical education environment and therefore persevere with their situation. In addition, lack of experience in health services can result in medical students using cynicism as a way of controlling their environment [41].…”
Section: Discussionmentioning
confidence: 99%
“…Entre os atributos do humanismo, o mais citado foi a empatia [16][17][18][19] . Os atributos inerentes ao humanismo médico variam entre culturas, sendo mais frequentes na cultura ocidental aqueles relacionados a competência clínica, comunicação, ética, humanismo, excelência, responsabilidade e altruísmo.…”
Section: Atributos Do Humanismounclassified
“…Alguns estudos sugerem que a empatia do estudante de Medicina decresce com o avanço dos anos de estudo, afetando a humanização da assistência 17 , porém outros não revelaram tal declínio 18,19 .…”
Section: Atributos Do Humanismounclassified
See 1 more Smart Citation